Collecting DNA from Juveniles in 30 U.S. States, 2009-2010 - Samuels, Julie ([Verlag nicht ermittelbar], 2014)
This study examined the laws, policies, and practices related to juvenile DNA collection, as well as their implications for the juvenile and criminal justice systems. DNA evidence proved valuable in solving crimes, which motivated a concerted effort to expand the categories of offenders who provided DNA samples for analysis and inclusion in the Combined DNA Index System (CODIS), the Federal Bureau of Investigation (FBI)-operated national database. State requirements for DNA collection, which initially focused on adult offenders convicted of sexual or violent offenses, expanded to include other categories of convicted felons, convicted misdemeanants, arrestees, and juveniles. In 30 states, certain categories of juveniles handled in the juvenile justice system must now provide DNA samples. The study was designed to explore the practice and implications of collecting DNA from juveniles and addressed the following questions: How have state agencies, juvenile justice agencies and state laboratories implemented juvenile DNA collection laws? What were the number and characteristics of juveniles with profiles included in CODIS? How have juvenile profiles in CODIS contributed to public safety or other justice outcomes? What improvements to policies and practices needed to be made? To examine these questions, researchers at the Urban Institute: (1) systematically reviewed all state DNA statutes; (2) conducted semi-structured interviews with CODIS lab representatives in states that collect DNA from juveniles to understand how the laws were implemented; (3) collected and analyzed descriptive data provided by these labs on the volume and characteristics of juvenile profiles in CODIS; (4) conducted semi-structured interviews with juvenile and criminal justice stakeholders in five case study states; and (5) convened a meeting of federal officials and experts from the forensic and juvenile justice committees to explore the broader impacts of juvenile DNA collection.